Remote work: Job satisfaction and productivity in local government – a case study of the municipality of Argos-Mycenae in Greece - Venetia, Frentzou; Nikolaos, Karfakis; Odysseas, Kopsidas; Michalis, Anastasiou (Edelweiss Applied Science and Technology, 2025)
The shift to remote work has significantly transformed modern workplaces, including public administration. This study examines the impact of remote work on job satisfaction and productivity in local government organizations (O.T.A.), focusing on a case study of the Municipality of Argos-Mycenae. A questionnaire survey of 120 municipal employees from Argos-Mycenae was conducted, utilizing descriptive and inferential statistical methods, including t-tests and one-way ANOVA. After coding the data, analysis was performed using SPSS version 26 software. The findings indicate that remote work enhances job satisfaction by providing flexibility and improving work-life balance. However, challenges such as technological limitations, communication barriers, and reduced managerial oversight negatively impact productivity. The study emphasizes the need for improved digital infrastructure, clear telecommuting policies, and ongoing employee training to optimize remote work in local government. This research contributes to the ongoing discussion on public sector telecommuting by offering practical recommendations for enhancing workplace efficiency while maintaining employee well-being. The findings can inform policymakers and municipal leaders in designing effective remote work strategies.